2016
DOI: 10.1111/add.13309
|View full text |Cite
|
Sign up to set email alerts
|

Re-starting smoking in the postpartum period after receiving a smoking cessation intervention: a systematic review

Abstract: Aims In pregnant smoking cessation trial participants, to estimate (1) among women abstinent at the end of pregnancy, the proportion who re-start smoking at time-points afterwards (primary analysis) and (2) among all trial participants, the proportion smoking at the end of pregnancy and at selected time-points during the postpartum period (secondary analysis). Methods Trials identified from two Cochrane reviews plus searches of Medline and EMBASE. Twenty-seven trials were included. The included trials were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 59 publications
(185 reference statements)
1
78
0
Order By: Relevance
“…Although the trial did not include a formal cost–utility analysis, it is highly likely that, if cessation is maintained in the longer term, the calculated ‘cost‐per‐quitter’ will translate into longer‐term cost‐effectiveness. One can assume that ‘quitters’ gain 1.94 quality‐adjusted life years (QALYs) across their life‐time 42, 43, so by multiplying this value by the seven additional quitters generated by MiQuit the incremental QALYs would be 13.58, making the incremental cost per additional QALY £69.06—even after inflating this figure to take into account relapse to smoking 44, this would remain securely within most accepted cost‐effectiveness benchmarks. Finally, it is noteworthy that the ‘non‐text‐message’ costs of MiQuit are fixed, and so ‘per‐user’ costs fall as the numbers using the intervention increase.…”
Section: Discussionmentioning
confidence: 99%
“…Although the trial did not include a formal cost–utility analysis, it is highly likely that, if cessation is maintained in the longer term, the calculated ‘cost‐per‐quitter’ will translate into longer‐term cost‐effectiveness. One can assume that ‘quitters’ gain 1.94 quality‐adjusted life years (QALYs) across their life‐time 42, 43, so by multiplying this value by the seven additional quitters generated by MiQuit the incremental QALYs would be 13.58, making the incremental cost per additional QALY £69.06—even after inflating this figure to take into account relapse to smoking 44, this would remain securely within most accepted cost‐effectiveness benchmarks. Finally, it is noteworthy that the ‘non‐text‐message’ costs of MiQuit are fixed, and so ‘per‐user’ costs fall as the numbers using the intervention increase.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, postpartum relapse rates of women who quit smoking during pregnancy are also high. A meta-analysis showed that 43% of women who stopped smoking during pregnancy began smoking again at 6 months postpartum [12]. In addition, subgroup analyses of this meta-analysis revealed that the rate of women who relapsed at 6 months postpartum increased to 74% when only studies with biochemically validated abstinence data were included [12].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, postpartum relapse prevention interventions have shown limited effects [2,17]. It seems that many women and their offspring do not receive the maximum health benefits of smoking cessation [12]. Therefore, there is still considerable room for improvement with regard to cessation and relapse-prevention interventions in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al [1] have clarified the present evidence regarding postnatal relapse to smoking. Future research must improve the quit rate by the end of pregnancy [15], but must also improve long-term cessation.…”
mentioning
confidence: 76%
“…Future research must improve the quit rate by the end of pregnancy [15], but must also improve long-term cessation. Future trials must have a postnatal component, as most relapse has happened by 6 months after birth, after which time cessation is likely to be long-lasting [1]. Permanent cessation will provide the maximum return for investment on effective smoking cessation interventions during pregnancy [14].…”
mentioning
confidence: 99%